PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASIONAL DENGAN MEDIASI PEMBERDAYAAN DI PT. PLN (PERSERO) RAYON DENPASAR - Meriani, Ni Made Kenasih; Sudibya, I Gede Adnyana (E-Jurnal Manajemen, 2016)
Organizational commitment is a strong feeling and strong of a person against an organization's goals and values in relation to their role towards achieving the objectives and values of the organization. This study aims to determine the effect of transformational leadership on organizational commitment to the empowerment of mediation in PT. PLN (Persero) Rayon Denpasar. This study uses a quantitative approach in the form of associative. This research was conducted at PT. PLN (Persero) Rayon Denpasar. Respondents in this study were taken from the overall population of 49 employees to exclude managers and supervisors. The analysis technique used in this study of the technique of path analysis (path analysis). Research shows that transformational leadership and significant positive effect on empowerment. Empowerment positive and significant effect on organizational commitment. Transformational leadership is positive and significant effect on organizational commitment. Empowerment mediate positive and significant influence of transformational leadership on organizational commitment.
Keywords: Transformational Leadership, Empowerment, Organizational Commitment